Queen's Royal College, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (James Book Store, 2010)
Exterior view of the front of the Queen’s Royal College (QRC), corner St. Clair Avenue and Maraval Road, Port of Spain, Trinidad. QRC was opened on March 25, 1904 at Queen's Park West by Governor Sir Alfred Maloney. This building was designed by Daniel M. Hahn, qualified architect and chief draughtsman in the Department of Public Works, who was a past student of the college. The late architect John Newel Lewis described the architecture of QRC as "a pastiche of Renaissance and Venetian details." Here we see the clock tower with the clock that was presented to the school in 1913 by William Gordon. The origin of QRC goes back to the Stuart Grammar School, at the corner of Duke and Edward Street. In 1870, the school became the Queen's Royal College and was housed at the Prince's Building. When the Government Farm moved from St Clair in 1899, part of the land was reserved as a new home for QRC through the intervention of acting Governor Sir Courtney Knollys (adapted from http://qrc.edu/about). Postcard number 14.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; [1925]; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; Schools--Trinidad and Tobago; High schools--Trinidad and Tobago; Public schools--Trinidad and Tobago; Education, Secondary--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture--Details; Towers--Trinidad and Tobago; Tower clocks--Trinidad and Tobago; Clocks and watches--Trinidad and Tobago; Windows--Trinidad and Tobago; Fences--Trinidad and Tobago; Palms--Trinidad and Tobago; Roads--Trinidad and Tobago; Magnificent Seven, The (Port of Spain); Queen's Park Savannah (Port of Spain); Queen's Royal College (Trinidad and Tobago)